Niat Ibu Memberi ASI Eksklusif Berdasarkan Theory of Planned Behavior - Marisa, Silva; Bratajaya, Cicilia Nony Ayuningsih (Universitas Faletehan, 2024)
Exclusive breastfeeding coverage in Indonesia had not reached the target yet. One of the things that determines the success of mothers in providing exclusive breastfeeding is intention. The study aimed to identify factors related to mother's intention to exclusive breastfeeding based on Theory of Planned Behavior (TPB). This quantitative study used a cross-sectional design. The population were mothers who had 0-6 months old babies. The purposive sampling technique was employed to 124 respondents. The TPB-based questionnaire was made up. The results of the study showed that majority of respondents (107 mothers or 86.3%) had a strong intention to exclusive breastfeeding. The result of data analysis using Kendall's Tau B showed that there was a relationship between attitudes (p-value = 0.000; p < 0.05), perceived perception control (p-value = 0.000; p < 0.05), and intention to exclusive breastfeeding. However, there was no relationship between subjective norms (p-value 0.723; p < 0.05) and intention to exclusive breastfeeding. Thus, health providers should enhance mothers’ awareness through health promotion, and breastfeeding facilities should be available to support exclusive breastfeeding coverage.